2011
DOI: 10.1007/s12602-011-9086-3
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus rhamnosus BFE 5264 and Lactobacillus plantarum NR74 Promote Cholesterol Excretion Through the Up-Regulation of ABCG5/8 in Caco-2 Cells

Abstract: The effect of two putative probiotic strains, Lactobacillus rhamnosus BFE5264 and Lactobacillus plantarum NR74, on the control of cholesterol efflux in enterocytes was assessed by focusing on the promotion of ATP-binding cassette sub-family G members 5 and 8 (ABCG5 and ABCG8). Differentiated Caco-2 enterocytes were treated with live bacteria, heat-killed bacteria, a bacterial cell wall fraction, and metabolites and were subjected to cholesterol uptake assay, mRNA analysis, and protein analyses. Following LXR-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 42 publications
(44 reference statements)
7
29
0
Order By: Relevance
“…The possibility, however, that the observed changes in sterol absorption may be a result of Niemann-Pick C1-like 1 transporter inhibition or a combination of cholesterol-reducing mechanisms should be considered. Yoon et al 46 reported that BSH-active Lactobacillus acting on Caco-2 cells resulted in the upregulation of LXR together with elevated expression of ABCG5/G8 transporters and increased cholesterol efflux without noticeable effects on Niemann-Pick C1-like 1 expression. In contrast, a study by Huang and Zheng 47 showed that the probiotic strain L. acidophilus ATCC 4356 reduced Niemann-Pick C1-like 1 gene expression and inhibited the cellular uptake of micellar cholesterol in Caco-2 cells, an effect at least partly mediated by LXR.…”
Section: Weekmentioning
confidence: 99%
“…The possibility, however, that the observed changes in sterol absorption may be a result of Niemann-Pick C1-like 1 transporter inhibition or a combination of cholesterol-reducing mechanisms should be considered. Yoon et al 46 reported that BSH-active Lactobacillus acting on Caco-2 cells resulted in the upregulation of LXR together with elevated expression of ABCG5/G8 transporters and increased cholesterol efflux without noticeable effects on Niemann-Pick C1-like 1 expression. In contrast, a study by Huang and Zheng 47 showed that the probiotic strain L. acidophilus ATCC 4356 reduced Niemann-Pick C1-like 1 gene expression and inhibited the cellular uptake of micellar cholesterol in Caco-2 cells, an effect at least partly mediated by LXR.…”
Section: Weekmentioning
confidence: 99%
“…plantarum NR74 also showed a up-regulating the expression of LXR and promotion of cholesterol efflux in Caco-2 cells [78]. This is identical to effect of bile acid sequestrants drug which can also induce an increase of LXR activity in liver [79].…”
Section: Nuclear Receptorsmentioning
confidence: 54%
“…Cholesterol uptake and efflux assays were already carried out by different groups, but the described methodology differs in regard to several assay conditions, i.e. differentiation of Caco-2 cells on plates with/without inserts, incubation with cholesterol packaged in micelles or not, composition of the micelles, incubation time and use/no use of acceptors like apoA1 [30][31][32][33][34]. Therefore, we also tested and adjusted these conditions for the cholesterol uptake and efflux assay.…”
Section: Establishing Functional Assays With Caco-2 Cells For Cholestmentioning
confidence: 99%